FORMATION RESEARCH COMPETENCE STUDENTS OF AGRARIAN UNIVERSITIES: USING THE METHOD OF MATHEMATICAL MODELING - Borozenets Nataliіa (Continuing Professional Education: Theory and Practice, 2020)
The article shows that mathematical disciplines are the foundation for the formation of research competence of students of agricultural universities. It was found that the willingness to use knowledge in mathematics is a prerequisite for obtaining a high-quality professional education, carrying out research activities. The definition of research competence of a specialist in the agricultural industry is given and the purpose of its formation among students-agrarians is indicated. It is proved that the formed research knowledge, abilities, skills, the acquired initial research experience in the mathematical plane should become the basis for the effective professional activity of a modern agrarian. It is shown that the content of the mathematical training of future agricultural specialists should be adjusted, and the knowledge of agricultural students in mathematical disciplines and the ability to use them in practice should be integral. The necessity of using the method of mathematical modeling in the process of forming research competence is substantiated, which provides for a balanced use of methods and teaching aids, forms of organizing students’ educational activities. The essence of mathematical modeling is considered, which is a set of all possible mathematical relationships that describe the main patterns, properties of the process, object or system under study, as well as tasks of mathematical modeling that appear when solving professional problems arising in the agricultural sector. The prerequisites for the use of mathematical models in the management of agricultural production are determined. The principles and requirements for mathematical models are generalized. The stages and methods of constructing mathematical models are highlighted. An example of applying the method of mathematical modeling in the course «Higher Mathematics» when studying the topic «Differential Equations of the 1st Order» is given. Conclusions are made on the application of the method of mathematical modeling to the formation of research competence of students-agrarians.